Ferrous iron transport via IRT1 evolved at least twice in green plants - Wenderson Felipe Costa Rodrigues (2022)
Iron (Fe) is an essential micronutrient for all living beings, being necessary for several metabolic activities and practically irreplaceable because it has unique electrochemical properties, which enable or facilitate a series of biochemical processes. Possibly, Fe was an essential element for the emergence of life on earth, since its use in essential biochemical processes is conserved throughout the evolution of living organisms. Currently on Earth, Fe is abundant, but it is found in a poorly soluble form (ferric iron – Fe3+) by living organisms such as plants. This scenario changes according to the environment, where, for example, in aquatic environments Fe is more bioavailable (as ferrous iron – Fe2+). Current plants have established Fe absorption strategies that are responses to the deficiency of this metal in the most soluble form. A. thaliana, for example, captures Fe through a mechanism that lowers the pH of the root region and increases the solubility of Fe3+, by pumping protons into the rhizosphere. The most soluble ferric Fe is reduced to ferrous Fe by FRO2 reductase and transported into the cell by the main iron transporter in plants, IRT1, belonging to the ZIP protein family (ZRT/IRT - Related Protein), composed of membrane transporters of Zn, Fe and other micronutrients. In this work, we investigate how Fe uptake mechanisms could possibly be one of the factors that led to terrestrialization of the planet by early streptophytes and how these Fe capture strategies were established during evolution in the plant lineage (Archaeplastida). Through phylogenetic analyses, we observed that the IRT1 of C. reinhardtii has sufficient distance from AtIRT1 to indicate a possible appearance in parallel and at different times in the evolutionary history of plants of these two types of IRT1. Furthermore, our comparative analyzes demonstrate that CrIRT1 amino acids are completely different in some essential positions for Fe transport to occur as in AtIRT1. With the results presented in this article, our work opens the way for different analyzes that can be used on top of the data found here, such as a structural and functional analysis of homologs of the ZIP family of algae species that have never been studied before. The functional and structural characterization of members of the ZIP family in Archaeplastida will help to understand how Fe absorption strategies were established in plants and will help in biotechnological studies in culture and health offered by these species.